Phytochemical And Antimicrobial Screening of The Stem-Bark and Leaf Extracts of Detarium Microcarpum (Leguminosae) - Ibrahim Jimoh; Abdullahi Jimoh; Sule M.O (Genius Journals, 2021)
The stem-bark and leaves of Detarium microcarpum which were selected on the basis of their use in traditional medicine to cure dysentery and diarrhoea were extracted with ethanol. The crude extracts were further partitioned with n-hexane, chloroform, ethyl acetate, methanol and water. The fractions were screened for phytochemicals and antimicrobial assay against Salmonella typhi and Staphylococcus aureus. The Salmonella typhi and Staphylococcus aureus were found resistant to all the fractions of the leaf of D. microcarpum at 15, 30 and 60µg/ml. The phytochemical screening revealed the presence of alkaloids, flavonoids, steroids, tannins, saponins and carbohydrates
Keywords: Stem-bark and leaves of Detarium microcarpum; phytochemicals and anti-microbial; ethanol